RESEARCH OF THE INFLUENCE OF MODERN TRENDS IN UI/ UX DESIGN OF MOBILE APPLICATIONS ON USER’S MOOD - A. S. Zhadan; O. O. Sichkar; D. A. Pishkin (Автоматизация технологических и бизнес-процессов)
Abstract: The research explores the impact of modern trends in UI/UX design on the mood of users interacting with mobile applications. Through an analysis of literature and a survey of IT students, the study evaluates the emotional resonance of seven contemporary UI/UX styles: brutalism, neubrutalism, Bauhaus, neumorphism, retrofuturism, cyberpunk, and glassmorphism. Each design trend is characterized by unique visual and functional elements that influence user experiences.